Pembuatan Sabun Cuci Tangan dengan Bahan Alami dan Langkah- Langkah Cara Mencuci Tangan dengan Benar - Hernawati; Sry Rejeki; Teti Febri Krisda Zebua (CV. Adiguna Kertosari, 2021)
The purpose of student service to the community for children is to conduct research on how to make hand soap with natural ingredients for the prevention of Covid-19 at the Sinergi Rasa Islamic Boarding School Foundation, located at Jl. Buaran Village No. 89 RT 02 RW 07 Kel. Buaran District. Serpong, Tangeran Selatan Banten 15310. This activity is expected to create small businesses to improve the economy of the community at the Sinergi Rasa Islamic Boarding School through the development of making handwashing soap with natural ingredients. The method in this PmKM activity is socialization.